Trade disciplines with a trapdoor: Contract manufacturing - Rudolf Adlung; Weiwei Zhang (World Trade Organization (WTO), 2012)
At first glance, this paper deals with a simple classification issue only: the coverage and treatment of certain manufacturing operations and the resulting products under the General Agreement on Trade in Services (GATS) rather than under its long-standing counterpart in merchandise trade, the General Agreement on Tariffs and Trade (GATT). Yet there are important structural/conceptual differences between the two Agreements, which may have far-reaching consequences, inter alia, for the use of GATT-based tariffs and trade remedies (anti-dumping and countervailing measures). It is submitted that the currently applied classification system could prompt companies to (re-)define the ownership conditions of otherwise identical production activities, with a view to avoiding GATT disciplines. However, the relevant criteria separating goods- from services-related operations are not only hard to specify and monitor in practice, but it is also difficult to see an underlying policy rationale. In the interest of clarity and consistency, WTO Members might thus want to close this conceptual trapdoor. Due to the rapid proliferation of international production-sharing arrangements, the stakes will likely be rising.
Keywords: F13; F53; 330; Trade in services (GATS); trade in goods (GATT); classification problems; Internationaler Dienstleistungsverkehr; WTO-Regeln; GATS